Food marketing in recreational sport settings in Canada: a cross-sectional audit in different policy environments using the Food and beverage Marketing Assessment Tool for Settings (FoodMATS) - Rachel J. L. Prowse; Patti-Jean Naylor; Dana Lee Olstad; Valerie Carson; Kate Storey; Louise C. Mâsse; Sara F. L. Kirk; Kim D. Raine (BMC, 2018)
Abstract Background Children's recreational sport settings typically sell energy dense, low nutrient products; however, it is unknown whether the same types of food and beverages are also marketed in these settings. Understanding food marketing in sports settings is important because the food industry often uses the promotion of physical activity to justify their products. This study aimed to document the 'exposure' and 'power' of food marketing present in public recreation facilities in Canada and assess differences between provinces with and without voluntary provincial nutrition guidelines for recreation facilities. Methods Food marketing was measured in 51 sites using the Food and beverage Marketing Assessment Tool for Settings (FoodMATS). The frequency and repetition ('exposure') of food marketing and the presence of select marketing techniques, including child-targeted, sports-related, size, and healthfulness ('power'), were assessed. Differences in 'exposure' and 'power' characteristics between sites in three guideline provinces (n = 34) and a non-guideline province (n = 17) were assessed using Pearson's Chi squared tests of homogeneity and Mann-Whitney U tests. Results Ninety-eight percent of sites had food marketing present. The frequency of food marketing per site did not differ between guideline and non-guideline provinces (median = 29; p = 0.576). Sites from guideline provinces had a significantly lower proportion of food marketing occasions that were "Least Healthy" (47.9%) than sites from the non-guideline province (73.5%; p < 0.001). Use of child-targeted and sports-related food marketing techniques was significantly higher in sites from guideline provinces (9.5% and 10.9%, respectively), than in the non-guideline province (1.9% and 4.5% respectively; p values < 0.001). It was more common in the non-guideline province to use child-targeted and sports-related techniques to promote "Least Healthy" items (100.0% and 68.4%, respectively), compared to the guideline provinces (59.3% and 52.0%, respectively). Conclusions Recreation facilities are a source of children's exposure to unhealthy food marketing. Having voluntary provincial nutrition guidelines that recommend provision of healthier foods was not related to the frequency of food marketing in recreation facilities but was associated with less frequent marketing of unhealthy foods. Policy makers should provide explicit food marketing regulations that complement provincial nutrition guidelines to fulfill their ethical responsibility to protect children and the settings where children spend time.